A STUDY OF CAPABILITY AND WILLINGNESS OF LOCAL SOCIETY TO FUND THE OPERATIONAL AND MAINTANANCE OF POLDER IN BANGER RIVER SEMARANG - Adi Jatmiko; Darmanto Darmanto; Sunjoto Sunjoto (Journal of the Civil Engineering Forum, 2014)
East Semarang District deals with a very serious problem for flood and robs threat. Rob is caused by high tide in the sea, while flooding caused by heavy rainfall. Banger River conveys run off flow from East Semarang District to the sea. Banger Polder System comprises dike surrounding Banger Polder and also dam aimed to protect it from rob attack, pump Station to control the water level, and retention pond used also as fishpond. To maintain urban polder management and flood protection system, society participation is highly. The purpose of this research was to determine the willingness and capability of communities to pay the operational and maintenance of polder system. Research focused on Banger Polder Area located at 10 Sub Districts in East Semarang District with the scope of discussion is to assess the society willingness-capability to pay the operational and maintenance of polder system. Primary data were collected by Contingent Valuation (CV) sample survey method using closed ended referendum elicitation format (Bidding game format), or closed questions by providing an alternative of answers choice. Society willingness in funding the operational and maintenance of polder can be determined by maximal costs that have been paid by society required to cope with flood and inundation problem in Semarang District. Society capability in funding polder operational and maintenance can be showed as a relation between total income and maximal capability of society in funding polder operational and maintenance. Result of data analysis showed that 87% society is categorized as capable society, and 12.67% society is incapable in funding polder operational maintenance. Result of data analysis showed that 81.33% society having the willingness, and 18.67% as the rest in paying the operational and maintenance of polder. Percentage of society which has the willingness and capability is approximately 72%. Income, building and land asset were used as decision variable in estimating participatory rates, fair, equitable, and independent which is expected to be sustained.Keywords: Social willingness, social capability, polder operational and maintenance costs.